pMEX01, a 70 kb plasmid isolated from Escherichia coli that confers resistance to multiple β-lactam antibiotics - Hernandez-Flores,Jose Luis (2018)
Abstract Multidrug-resistant microorganisms are of great concern to public health. Genetic mobile elements, such as plasmids, are among the most relevant mechanisms by which bacteria achieve this resistance. We obtained an Escherichia coli strain CM6, isolated from cattle presenting severe diarrheic symptoms in the State of Querétaro, Mexico. It was found to contain a 70 kb plasmid (pMEX01) with a high similarity to the pHK01-like plasmids that were previously identified and described in Hong Kong. Analysis of the pMEX01 sequence revealed the presence of a blaCTX-M-14 gene, which is responsible for conferring resistance to multiple β-lactam antibiotics. Several genes putatively involved in the conjugative transfer were also identified on the plasmid. The strain CM6 is of high epidemiological concern because it not only displays resistance to multiple β-lactam antibiotics but also to other kinds of antibiotics.